Effects of Crisis on Income and Poverty: The Case of Kazakhstan - Alma Kudebayeva (The Vienna Institute for International Economic Studies (wiiw), 2012)
This study investigates the effects of growth and crisis on poverty and distribution of consumption expenditures in Kazakhstan. Considerations include application and estimation of decomposed changes in poverty on components of growth and distribution. A comparison of the determinants for of vulnerability to impoverished households encompasses of prosperity and financial crisis during 2007 and 2009. This study evaluates the dynamics of changes in consumption patterns of households, along with the effects of Anti-Crisis policies implemented by the government of Kazakhstan.
Keywords: 330; Income; poverty; Kazakhstan